"All faiths and none"? An Audit of Chaplains' Visits. (25th May 2015) - Unknown
Abstract : Nearly 10, 000 records of visits by members of the Department of Spiritual Health Care to patients in St Thomas' and the Evelina London Children's Hospitals were analysed. Less than one percent of patients proactively sought support from the Department. Department initiated visits raised this to over three percent, with each patient being visited nearly three times on average. Increasing the availability and awareness of Muslim and Buddhist care providers resulted in a higher proportion of visits to patients with these religious beliefs. Despite nearly a quarter to half of all patients not being religious, only four percent of visits were to these patients. This indicates that the pastoral and spiritual needs of many patients who were not religious were not being met. This should be a serious cause for concern.